PERHITUNGAN STRUKTUR JEMBATAN BETON BERTULANG DESA TOKO LIMA - ANSYAH, ARDI (KURVA S JURNAL MAHASISWA, 2013)
Transportation is an important part of human life and developingmechanisms in line with the human civilization itself. One part is a transportbridge. The bridge is an important element in the transportation system, serving asa bridge serves traffic flow on it.Seeing the importance of the function of a bridge then the bridgeconstruction must meet a wide range of existing standards. construction ofhighway bridges with short spans, reinforced concrete construction should be usedas the main girder.Long span reinforced concrete bridge being simulated is 15,4 m,width 7 m carriageway, pavement width of 1 m and 1 m right side of the left side,so that the total width of the bridge 9 m. Results of analysis of reinforced concretebridge calculation is derived calculations use the floor slab reinforcement D16 -100 for flexural reinforcement and negative reinforcement D16 - 150 for flexuralpositive. Backrest using reinforcement 2Ã˜12 pole. the girder plans drawn ultimatemoment (Mu) of 3286.78 kNm and shear girder ultimate plan is 728.18 kN.Girder reinforcement is used by 14 D 32. To ensure that the girder is ductile, thenpress the reinforcement is taken by 30% tensile reinforcement, so the use ofreinforcement 4 D 32. Reinforcement steel piles by 16 D 19 mm with spiral shearreinforcement used cross section D Ã˜ 12 mm